Механіка елементів хвильового рушія - Лисих, А. Ю.; Lisikh, Alla (КНТУ, 2015)
Розглянуто метод числового розв’язання задачі коливання гнучкої пластини, що є складовою частиною рушія підводного робота. Для розв’язання задачі побудована система звичайних диференціальних рівнянь з нелінійними початковими умовами, порядок якої за допомогою перших інтегралів зменшений до дванадцяти. Розв’язки отримані модифікованим методом Коші із застосуванням методу продовження розв’язання за параметром. Наведено результати числових розрахунків. Resilient deformation of flexible flat element of the marine setting is considered in the article, it is indicated on actuality of decision of this question. The method of numerical decision of task of oscillation is offered with variable tensions of technological submarine robot which allows to get necessary descriptions of the tensely-deformed state of flexible object. For the decision of nonlinear regional task the method of continuation is used on a parameter. Such approach allows effectively to use computational algorithms for the timely change of problem specification depending on technological necessities. By means of this methods it is possible to get any factors of the tenselydeformed state at loading of arbitrary vector of loading of both static and dynamic character, to optimize the form of dvigitelya and others like that. Examples of decision of such tasks which allow to draw conclusion about authenticity and efficiency of the used methods are made in the article. The results of decision given in the article as computer graphics underline their authenticity, as one of signs of rightness of the got numerical decisions is convergence of differential equalizations. The worked out methods and algorithms can be useful at development of new constructions of submarine technological robots.
Mechanics of elements of dvigitelya
Keywords: рушій; гнучкий елемент; метод продовження за параметром; числове інтегрування; flexible element; method of continuation on a parameter; numerical integration